The Relationship between Motivation, Self-Management and Self-Competence with Procrastination Behavior in Futsal Athletes at Politeknik Negeri Sriwijaya (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Sports psychology, especially concerning athlete behavior, is the basis for determining athletes' characteristics and performance so that it can affect the development and achievement of athletes in the future. An athlete must be viewed individually because the personality of each athlete is different. The research objective was to analyze the relationship between motivation, self-management, and self-competence with procrastination behavior. The research method used a mixed-method non-experimental approach using a sequential explanatory strategy. The population of 35 athletes, sampling using total sampling, data analysis using Pearson product-moment correlation, and multiple regression with SPSS 25. The results showed a relationship between motivation and procrastination behavior (r = 0.153), self-management with procrastination behavior (r = 0.483), self-competence with procrastination behavior (r = 0.542), motivation and self-management with procrastination behavior (r = 0.483), motivation and self-competence with procrastination behavior (r = 0.557), self-management and self-competence with procrastination behavior (r = 0.653), self-management motivation and self-competence with procrastination behavior (r = 0.653). The conclusion proves that there is a very low relationship between motivation and procrastination behavior, there is a sufficient relationship between self-management and procrastination behavior, there is a strong relationship between self-competence and procrastination behavior, there is an adequate relationship between motivation and self-management with procrastination behavior there is a strong relationship between motivation and procrastination behavior. Self-competence with athlete procrastination behavior is a strong relationship between self-management and self-competence with athlete's procrastination behavior. There is a strong relationship between motivation, self-management, and self-competence with procrastination behavior in futsal athletes at Politeknik Negeri Sriwijaya in 2020.